Prescribing and medication initiation roles based on the perspectives of rural healthcare providers in a study community in Queensland - Tan, A.; Emmerton, Lynne; Hattingh, H. Laetitia (CSIRO Publishing, 2013)
Objective. There are recognised health service inequities in rural communities, including the timely provision of medications, often due to shortages of qualified prescribers. The present paper explores the insights of rural healthcare providers into the prescribing and medication-initiation roles of health professionals for their rural community. Methods. Forty-nine healthcare providers (medical practitioners, pharmacists, nurses, occupational therapists, a dentist and an optometrist) from four neighbouring towns in a rural health service district in Queensland participated in face-to-face semistructured interviews. The interviews explored medication supply and management issues in the community, including the roles of health professionals to address these issues. The interviews, averaging 45 min in duration, were recorded, transcribed and qualitatively analysed for general trends and unique responses. Results. Participants recognised the potential for dentists, optometrists and nurse practitioners to reduce the prescribing workload of rural medical practitioners, and there was some support for a ‘continued dispensing’ model for pharmacists. Medication-initiation orders by endorsed registered nurses were also valued in providing timely medical treatment in rural hospitals. Conclusions. Rural communities have unique needs that require consideration of multidisciplinary support to assist medical practitioners in coping with prescription demands for timely medical treatment.